2020
DOI: 10.3390/ijgi9020071
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Hazard Compensations Based on Land Administration Data

Abstract: During the summer period, fire hazards represent an especially real threat not only for vegetation and animals, but also for material resources and human lives. In the Republic of Croatia, the most affected areas are those in the coastal region, which are characterised by a very dry environment and strong winds that are conducive to the rapid spread of wildfire. Although the prevention of wildfire is an utmost imperative, many countries are still missing a good and reliable fire management system for both fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They aimed at ensuring the accessibility for residents and communicating the risks via geovisualization. Vučić et al (2020) demonstrated the efficiency of GIS and web technologies for post-disaster assessment after wildfires. Sylka et al (2018) mapped the damages in vineyards after a hailstorm using spatial analysis methods on WebGIS.…”
Section: Related Workmentioning
confidence: 99%
“…They aimed at ensuring the accessibility for residents and communicating the risks via geovisualization. Vučić et al (2020) demonstrated the efficiency of GIS and web technologies for post-disaster assessment after wildfires. Sylka et al (2018) mapped the damages in vineyards after a hailstorm using spatial analysis methods on WebGIS.…”
Section: Related Workmentioning
confidence: 99%
“…During the summer period, fire hazards represent an especially severe threat, not only for vegetation and animals, but also for material resources and human lives. In Croatia, the most affected areas are those in the coastal region, which are characterized by a very dry environment and strong winds, which are conducive to the rapid spread of wildfire [24]. In recent research on the Croatian territory, some solutions have been provided regarding the determination of hazard compensations based on land administration data.…”
Section: Fire Hazardsmentioning
confidence: 99%